A composite multi-effect scale and corrosion inhibitor and preparation method thereof

By preparing a composite multi-effect scale-resistance corrosion inhibitor containing multiple functional components, the problem that the prior art is difficult to ensure scale-resistance and corrosion inhibition under high concentration ratio conditions is solved, and high-efficiency scale-resistance and corrosion inhibition effects are achieved under high pH, ​​high alkalinity, high temperature and high hardness conditions.

CN119263505BActive Publication Date: 2025-04-01ANHUI HAIHAN WATER TREATMENT TECH CO LTD

Patent Information

Application Number
CN202411806213.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-01
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing high-phosphorus-based scale inhibitors cause eutrophication of water bodies. Low-phosphorus-free scale inhibitors are difficult to ensure scale inhibition and corrosion inhibition under high concentration multiple operating conditions, and cannot meet the complex needs of industrial circulation cooling water systems.

Method used

A composite multi-effect scale-resistance corrosion inhibitor is prepared by synthesis and compounding method, containing carboxylic acid monomers, sulfonate monomers, organophosphorus compounds, modified chitosan, modified nanotitanium dioxide, oxidation initiators, reducing initiators, azole derivatives and regulators to enhance its scale-resistance and corrosion inhibition properties under high pH, ​​high alkalinity, high temperature and high hardness.

Benefits of technology

Under the operating conditions of higher concentration ratios, this composite multi-effect scale-resistance inhibitor significantly improves the scale-resistance rate of calcium carbonate and calcium phosphate, ensures the long-term and stable operation of the equipment, reduces maintenance costs, and has green and environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a composite multi-effect scale inhibitor and a preparation method thereof, belonging to the technical field of water treatment agents. The composite multi-effect scale inhibitor uses carboxylic acid monomers, sulfonate monomers, organic phosphorus compounds, modified chitosan, modified nano titanium dioxide, oxidative initiators, reduced initiators, azole derivatives and other ingredients as raw materials, wherein the modified chitosan is chitosan surface coated with cerium chloride; the modified nano titanium dioxide is nano titanium dioxide surface coated with sodium polyaspartate. The composite multi-effect scale inhibitor is prepared by a synthesis and compounding method, has excellent scale inhibition effect, and the comprehensive scale removal capacity can reach more than 97%. It can be used in high pH, ​​high alkalinity, high temperature and high hardness circulating cooling water systems under high concentration multiples operating conditions, and is suitable for circulating cooling water treatment requirements under harsh conditions in industries such as chemical industry, smelting and light industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment agents, and in particular relates to a composite multi-effect scale and corrosion inhibitor and a preparation method thereof. Background Art

[0002] Scale inhibitor is a water treatment agent. It can prevent scale-forming substances such as calcium and magnesium in water from scaling on the surface of equipment (such as heat exchangers, inner walls of pipes, etc.). For example, in industrial circulating cooling water systems, water is continuously recycled, and scale is easily formed when the concentration of calcium, magnesium and other ions increases. Scale inhibitors can keep these ions in a dispersed state through chelation and dispersion, thereby preventing scale from forming, extending the service life of equipment, and improving the heat transfer efficiency of equipment.

[0003] In modern industrial production, the amount of cooling water used in factory equipment is extremely large. In the circulating cooling water system, cooling water is in a state of continuous circulation. In this process, a series of problems gradually emerge. On the one hand, the water temperature rises, the water flow rate changes, the water evaporates, etc., which leads to the continuous concentration of various inorganic ions and organic substances, the concentration of harmful ion components continues to increase, and the water quality deteriorates. Among them, the scaling problem of calcium carbonate, calcium phosphate, etc. is becoming more and more serious. These scales will accumulate on the surface of the equipment, such as heat exchangers, the inner wall of the pipe and other key parts, seriously threatening and destroying the long-term stable operation of the equipment. Once the equipment fails due to scaling, the maintenance cost is high, and it may even cause the factory to face serious economic losses.

[0004] From the perspective of environmental protection and sustainable development, there are some studies on phosphorus-free or low-phosphorus water treatment solutions in China. For example, a corrosion and scale inhibitor and its preparation method and use method disclosed in the invention patent with publication number CN104193016A, a phosphorus-free scale and corrosion inhibitor disclosed in the invention patent with publication number CN110937698A, and a composite phosphorus-free scale inhibitor and its preparation method in the invention patent with publication number CN116040820A; however, these studies have limitations. When used in the natural operation process of pH value, although corrosion inhibition is relatively easy to control, the concentration multiple is often low. Under the operating conditions of higher concentration multiples, the zinc salt concentration required for phosphorus-free corrosion inhibition is high, but the corrosion inhibition effect is difficult to guarantee. Therefore, the current industry has extremely high requirements for scale and corrosion inhibitors. It is not only expected to have efficient scale and corrosion inhibition capabilities, but also to achieve multiple effects with one dose to cope with the complex and demanding needs of industrial circulating cooling water treatment. Summary of the invention

[0005] The phosphorus discharge of existing high-phosphorus scale inhibitors has caused serious eutrophication of water bodies, and the scale and corrosion inhibition capabilities of low-phosphorus and phosphorus-free scale inhibitors are difficult to guarantee in high-pH, high-alkalinity, high-temperature and high-hardness circulating cooling water systems under high concentration multiples operating conditions. The present invention provides a composite multi-effect scale inhibitor and a preparation method thereof, which uses carboxylic acid monomers, sulfonate monomers, organic phosphorus compounds, modified chitosan, modified nano-titanium dioxide, oxidative initiators, reduced initiators, azole derivatives, etc. as raw materials, and adopts a synthesis and compounding method to prepare the composite multi-effect scale inhibitor. The scale inhibition effect is excellent, and it can be used in high-pH, high-alkalinity, high-temperature and high-hardness circulating cooling water systems under high concentration multiples operating conditions. It is suitable for the circulating cooling water treatment requirements under harsh conditions in industries such as chemical, smelting and light industry. The specific technical scheme is as follows:

[0006] A composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 5 to 15 parts of carboxylic acid monomers, 15 to 30 parts of sulfonate monomers, 10 to 20 parts of organic phosphorus compounds, 1 to 3 parts of modified chitosan, 2 to 6 parts of modified nano titanium dioxide, 1 to 5 parts of oxidative initiators, 1 to 5 parts of reduced initiators, 1 to 5 parts of azole derivatives, 5 to 10 parts of regulators and 0 to 30 parts of purified water.

[0007] In the above technical scheme, the preparation method of the modified chitosan comprises the following steps: according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = (8-12): (0.5-2): (0.2-0.4): (100-120), cerium chloride and glutaraldehyde are added into water for uniform dissolution, then chitosan is added, ultrasonic dispersion is performed for uniform mixing, centrifugation is performed, solid is taken, dried and then broken up to obtain modified chitosan.

[0008] In the preparation method of the modified chitosan, the chitosan is high molecular weight chitosan with a molecular weight range of 100,000 Da to 300,000 Da; the frequency of the ultrasound is 20kHz to 40kHz, the speed of the centrifugal separation is 6000r / min to 10000r / min, and the time of the centrifugal separation is 15min to 25min.

[0009] In the above technical scheme, the preparation method of the modified nano titanium dioxide is as follows: according to the mass ratio of nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = (5-8): (0.3-0.8): (0.08-0.2): (100-120), sodium polyaspartate is dissolved in 5-10 parts of water to form a sodium polyaspartate aqueous solution; then the nano titanium dioxide is ultrasonically dispersed in the remaining part of water to form a suspension, and then glutaraldehyde is added and ultrasonically dissolved uniformly, and then the sodium polyaspartate aqueous solution is added, ultrasonically mixed uniformly, centrifuged, and the solid is taken, dried and then dispersed to obtain the modified nano titanium dioxide.

[0010] In the above-mentioned preparation method of modified nano-titanium dioxide, the frequency of the ultrasound is 20kHz to 40kHz, the rotation speed of the centrifugal separation is 10000r / min to 12000r / min, and the time of the centrifugal separation is 15min to 25min.

[0011] In the above technical solution, the carboxylic acid monomer is at least one of acrylic acid (AA) and maleic acid (MA).

[0012] In the above technical solution, the sulfonate monomer is at least one of sodium allyl sulfonate (SAS), sodium styrene sulfonate (SS), 2-acrylamido-2-methylpropane sulfonic acid (AMPS), and sodium methyl allyl sulfonate (SMAS).

[0013] In the above technical solution, the organic phosphorus compound is at least one of aminotrimethylenephosphonic acid (ATMP), 2-hydroxyphosphonoacetic acid (HPAA), hydroxyethylidene diphosphonic acid (HEDP), and 2-phospho-1,2,4-tricarboxylic acid butane (PBTCA).

[0014] In the above technical solution, the oxidative initiator is at least one of sodium persulfate, ammonium persulfate and hydrogen peroxide.

[0015] In the above technical solution, the reducing initiator is at least one of sodium bisulfite, ferrous sulfate, sodium hypophosphite and ascorbic acid.

[0016] In the above technical solution, the azole derivative is at least one of tolutriazole (TTA), benzotriazole (BTA), and mercaptobenzothiazole (MBT).

[0017] In the above technical solution, the regulator is at least one of isopropanol, dodecyl mercaptan, ethylene glycol and mercaptoethanol.

[0018] The preparation method of the composite multi-effect scale and corrosion inhibitor comprises the following steps:

[0019] S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A;

[0020] S2: Stir and mix the carboxylic acid monomer, reduced initiator and purified water according to their mass fractions, raise the temperature to 50°C-55°C, add the regulator and stir and mix evenly, continue to heat to 70°C-75°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to be within 50min-60min, continue to stir and react for 3h-3.5h, cool to room temperature, add the azole derivative, stir and mix for 20min-40min, filter through a 100-mesh-150-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor.

[0021] The composite multi-effect scale and corrosion inhibitor of the present invention and its preparation method have the following beneficial effects:

[0022] 1. The composite multi-effect scale and corrosion inhibitor of the present invention contains carboxylic acid monomers, sulfonate monomers, organic phosphorus compounds, modified chitosan, modified nano titanium dioxide, oxidative initiators, reduced initiators, azole derivatives, regulators and other ingredients. Under the action of oxidative initiators and reduced initiators, the unsaturated bonds (such as carbon-carbon double bonds) in the carboxylic acid monomers and sulfonate monomers are opened, and the two are connected to form a long polymer chain to generate a polymer containing carboxyl and sulfonic acid groups. The carboxyl group can chelate with metal ions (such as calcium and magnesium ions) in water to reduce the concentration of free metal ions in water and reduce the possibility of scaling; the sulfonic acid group can enhance the solubility and dispersibility of the polymer in water, and at the same time give the product a certain charge property, which helps to prevent particle aggregation; the generated polymer can be adsorbed on the surface of solid particles suspended in water. Due to steric hindrance and charge repulsion, the particles are prevented from agglomerating and precipitating, so that they are stably dispersed in water and avoid deposition on the surface of the equipment. Organic phosphorus compounds react with metal surfaces to form a protective film, which reduces the contact between the metal surface and corrosive media such as dissolved oxygen and hydrogen ions in water, and indirectly reduces scaling caused by corrosion products, which inhibits the formation of calcium carbonate and calcium phosphate scale. Modified chitosan: After the surface of chitosan is coated with cerium chloride, the adsorption performance is enhanced, and it can be adsorbed on the metal surface. Physical adsorption blocks the contact between corrosive media and metals. Chemical adsorption combines with metal ions through its active groups, and can also adsorb impurities and scale precursors in water, thereby improving the scale inhibition rate of calcium carbonate and calcium phosphate. Modified nano titanium dioxide: After the surface of nano titanium dioxide is coated with sodium polyaspartate, it has stronger adsorption performance, reduces scale formation, and enhances the compactness of the protective film, which is beneficial to improve the scale inhibition rate of calcium carbonate and calcium phosphate. Azole derivatives are mainly used to inhibit metal corrosion, reduce scaling caused by metal corrosion products, and indirectly improve the scale inhibition rate of calcium carbonate and calcium phosphate. The regulator can adjust the pH and stability of the reagent system to ensure that the reagent is evenly dispersed in the water, which is conducive to the other ingredients to fully exert their scale inhibition effect and has an auxiliary effect on improving the scale inhibition rate of calcium carbonate and calcium phosphate.

[0023] 2. Advantages of modified chitosan over chitosan: The surface of modified chitosan is coated with cerium chloride, which enhances its dispersibility in water, allowing it to be more evenly distributed in water and better contact the metal surface and scale precursors. The coating of cerium chloride increases the binding sites and binding force between chitosan and metal ions, enhancing its adsorption performance, thereby more effectively preventing the formation of scale and adsorption on the metal surface, and exerting better scale and corrosion inhibition effects.

[0024] 3. Advantages of modified nano-titanium dioxide over nano-titanium dioxide: After the surface of nano-titanium dioxide is coated with sodium polyaspartate, sodium polyaspartate improves the absorption and utilization efficiency of nano-titanium dioxide to light, and enhances its ability to decompose organic scale precursors during the photocatalytic process. The coated modified nano-titanium dioxide has better dispersibility in water, which is more conducive to its filling in the pores of the protective film, enhancing the compactness of the protective film and improving the corrosion and scale inhibition performance.

[0025] 4. The combination of modified chitosan and modified nano-titanium dioxide has a synergistic scale inhibition effect, enhances the performance of the protective film, and improves the dispersion and stabilization effect. Modified chitosan can adsorb impurities and scale precursors in water to prevent them from depositing and forming scale. Modified nano-titanium dioxide can decompose organic scale precursors in water under light conditions and reduce the generation of scale. The combination of the two can inhibit the formation of scale from different angles, produce a synergistic inhibitory effect on the formation of scales such as calcium carbonate and calcium phosphate, and enhance the overall scale inhibition effect. Modified chitosan can be adsorbed on the metal surface, form a protective film through physical and chemical adsorption, and block the contact between corrosive media and metals. Modified nano-titanium dioxide can fill in the tiny pores of the protective film to enhance the density of the protective film. They work together to build a stronger and denser protective film, effectively isolating the metal from corrosive substances and scale components in water, which not only improves the corrosion inhibition performance, but also reduces the adhesion of scale on the metal surface. Modified nano-titanium dioxide has good dispersibility in water, and modified chitosan can also help stabilize the dispersed system to a certain extent. The combination of the two can make the entire scale inhibitor more evenly dispersed in the water, ensuring that each component can fully exert its role, better interact with calcium, magnesium ions and scale particles in the water, and improve the scale inhibition efficiency of calcium carbonate and calcium phosphate.

[0026] 5. Azole derivatives focus on inhibiting metal corrosion, reducing scaling caused by corrosion products, thereby reducing the formation of scale, and reducing the risk of scaling caused by metal corrosion, thereby improving the scale inhibition effect in all aspects.

[0027] 6. Adding oxidative initiators and reducing initiators is mainly used to initiate the polymerization reaction of carboxylic acid monomers and other ingredients, so that the active ingredients of the agent can be better combined to form polymers with suitable molecular weight and structure. Suitable molecular weight and structure help improve the scale and corrosion inhibition performance of the agent, enable the polymer to be better dispersed in water and interact with metal ions and scale, and improve the overall performance of the agent.

[0028] 7. The composite multi-effect scale inhibitor and corrosion inhibitor of the present invention can be used in high pH, ​​high alkalinity, high temperature and high hardness circulating cooling water systems under high concentration multiples operating conditions, and is suitable for circulating cooling water treatment requirements under harsh conditions in industries such as chemical, smelting and light industry. Organic phosphorus has good chemical stability and is not easily hydrolyzed when used in a high temperature environment, thus not causing excessive reproduction of bacteria and algae, and has green and environmentally friendly characteristics. The composite multi-effect scale inhibitor and corrosion inhibitor has multiple functional groups that synergize and enhance the effect, and one dose has multiple effects. The composite multi-effect scale inhibitor and corrosion inhibitor is prepared by a method of synthesis and compounding. The process is simple and easy to operate. It is a scale inhibitor synthesis preparation method that is easy to industrialize. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0030] Example 1

[0031] A composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 10 parts of carboxylic acid monomers, 22 parts of sulfonate monomers, 15 parts of organic phosphorus compounds, 2 parts of modified chitosan, 4 parts of modified nano titanium dioxide, 3 parts of oxidative initiators, 3 parts of reduced initiators, 3 parts of azole derivatives, 8 parts of regulators and 15 parts of purified water.

[0032] The preparation method of modified chitosan comprises the following steps: using chitosan with a molecular weight range of 100,000 Da to 300,000 Da as a raw material; adding cerium chloride and glutaraldehyde into water to dissolve them uniformly according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = 10:1:0.3:110, then adding chitosan, mixing them uniformly with 30kHz ultrasonic dispersion, centrifuging at 8000r / min for 20min, taking the solid, drying and breaking it up to obtain modified chitosan.

[0033] In the above technical scheme, the preparation method of the modified nano titanium dioxide is as follows: according to the mass ratio of nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = 6:0.5:0.1:110, sodium polyaspartate is dissolved in 8 parts of water to form a sodium polyaspartate aqueous solution; then the nano titanium dioxide is ultrasonically dispersed in the remaining part of water at 30kHz to form a suspension, and then glutaraldehyde is added and ultrasonically dissolved at 30kHz to uniformly dissolve, and then the sodium polyaspartate aqueous solution is added, and ultrasonically mixed at 30kHz to uniformly mix, and centrifuged at 11000r / min for 20min, and the solid is taken, dried and dispersed to obtain the modified nano titanium dioxide.

[0034] Among them, the carboxylic acid monomer is acrylic acid (AA). The sulfonate monomer is sodium allyl sulfonate (SAS). The organic phosphorus compound is aminotrimethylenephosphonic acid (ATMP). The oxidative initiator is sodium persulfate. The reducing initiator is sodium bisulfite. The azole derivative is methyl benzotriazole (TTA). The regulator is isopropyl alcohol.

[0035] The preparation method of the composite multi-effect scale and corrosion inhibitor comprises the following steps:

[0036] S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A;

[0037] S2: Stir and mix the carboxylic acid monomer, reduced initiator and purified water according to their mass fractions, raise the temperature to 50°C, add the regulator and stir and mix evenly, continue to heat to 70°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to complete the dropping within 60 min, continue stirring and reacting for 3 h, cool to room temperature, add the azole derivative, stir and mix for 30 min, filter through a 100-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor and corrosion inhibitor.

[0038] Example 2

[0039] A composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 5 parts of carboxylic acid monomers, 15 parts of sulfonate monomers, 10 parts of organic phosphorus compounds, 1 part of modified chitosan, 2 parts of modified nano titanium dioxide, 1 part of oxidative initiator, 1 part of reduced initiator, 1 part of azole derivatives, 5 parts of regulators and 8 parts of purified water.

[0040] The preparation method of modified chitosan comprises the following steps: using chitosan with a molecular weight range of 100,000 Da to 300,000 Da as a raw material; adding cerium chloride and glutaraldehyde into water to dissolve them uniformly according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = 8:0.5:0.2:100, then adding chitosan, mixing them uniformly by 20kHz ultrasonic dispersion, centrifuging at 6000r / min for 15 minutes, taking the solid, drying and breaking it up to obtain modified chitosan.

[0041] In the above technical scheme, the preparation method of the modified nano titanium dioxide is as follows: according to the mass ratio of nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = 5:0.3:0.08:100, sodium polyaspartate is dissolved in 5 parts of water to form a sodium polyaspartate aqueous solution; then the nano titanium dioxide is ultrasonically dispersed in the remaining part of water at 20kHz to form a suspension, and then glutaraldehyde is added and dissolved evenly at 20kHz ultrasound, and then the sodium polyaspartate aqueous solution is added, and mixed evenly at 20kHz ultrasound, and centrifuged at 10000r / min for 15min, and the solid is taken, dried and dispersed to obtain the modified nano titanium dioxide.

[0042] Among them, the carboxylic acid monomer is maleic acid (MA). The sulfonate monomer is sodium styrene sulfonate (SS). The organic phosphorus compound is 2-hydroxyphosphonoacetic acid (HPAA). The oxidative initiator is ammonium persulfate. The reducing initiator is ferrous sulfate. The azole derivative is benzotriazole (BTA). The regulator is dodecyl mercaptan.

[0043] The preparation method of the composite multi-effect scale and corrosion inhibitor comprises the following steps:

[0044] S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A;

[0045] S2: Stir and mix the carboxylic acid monomer, reduced initiator and purified water according to their mass fractions, heat to 52°C, add the regulator and stir and mix evenly, continue to heat to 72°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to complete the dropping within 55 min, continue stirring and reacting for 3 h, cool to room temperature, add the azole derivative, stir and mix for 20 min, filter through a 100-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor and corrosion inhibitor.

[0046] Example 3

[0047] A composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 5 parts of carboxylic acid monomers, 30 parts of sulfonate monomers, 10 parts of organic phosphorus compounds, 3 parts of modified chitosan, 2 parts of modified nano titanium dioxide, 5 parts of oxidative initiators, 1 part of reduced initiators, 5 parts of azole derivatives, 5 parts of regulators and 20 parts of purified water.

[0048] The preparation method of modified chitosan comprises the following steps: using chitosan with a molecular weight range of 100,000 Da to 300,000 Da as a raw material; adding cerium chloride and glutaraldehyde into water to dissolve them uniformly according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = 8:2:0.2:120, then adding chitosan, mixing them uniformly with 20kHz ultrasonic dispersion, centrifuging at 6000r / min for 25min, taking the solid, drying and breaking it up to obtain modified chitosan.

[0049] In the above technical scheme, the preparation method of the modified nano titanium dioxide is as follows: according to the mass ratio of nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = 5:0.8:0.08:120, sodium polyaspartate is dissolved in 5 parts of water to form a sodium polyaspartate aqueous solution; then the nano titanium dioxide is ultrasonically dispersed in the remaining part of water at 40kHz to form a suspension, and then glutaraldehyde is added and dissolved evenly at 40kHz ultrasound, and then the sodium polyaspartate aqueous solution is added, and mixed evenly at 40kHz ultrasound, and centrifuged at 10000r / min for 25min, and the solid is taken, dried and dispersed to obtain the modified nano titanium dioxide.

[0050] The carboxylic acid monomer is a mixture of acrylic acid (AA) and maleic acid (MA) in equal amounts. The sulfonate monomer is 2-acrylamido-2-methylpropanesulfonic acid (AMPS). The organophosphorus compound is hydroxyethylidene diphosphonic acid (HEDP). The oxidative initiator is hydrogen peroxide. The reducing initiator is sodium hypophosphite. The azole derivative is mercaptobenzothiazole (MBT). The regulator is ethylene glycol.

[0051] The preparation method of the composite multi-effect scale and corrosion inhibitor comprises the following steps:

[0052] S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A;

[0053] S2: Stir and mix the carboxylic acid monomer, reduced initiator and purified water according to their mass fractions, heat to 50°C, add the regulator and stir and mix evenly, continue to heat to 75°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to complete the dropping within 50 min, continue stirring and reacting for 3.5 h, cool to room temperature, add the azole derivative, stir and mix for 20 min, filter through a 150-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor.

[0054] Example 4

[0055] A composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 15 parts of carboxylic acid monomers, 30 parts of sulfonate monomers, 20 parts of organic phosphorus compounds, 3 parts of modified chitosan, 6 parts of modified nano titanium dioxide, 5 parts of oxidative initiators, 5 parts of reduced initiators, 5 parts of azole derivatives, 10 parts of regulators and 30 parts of purified water.

[0056] The preparation method of modified chitosan comprises the following steps: using chitosan with a molecular weight range of 100,000 Da to 300,000 Da as a raw material; adding cerium chloride and glutaraldehyde into water to dissolve them uniformly according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = 12:2:0.4:120, then adding chitosan, mixing them uniformly with 40kHz ultrasonic dispersion, centrifuging at 10000r / min for 25min, taking the solid, drying and breaking it up to obtain modified chitosan.

[0057] In the above technical scheme, the preparation method of the modified nano titanium dioxide is as follows: according to the mass ratio of nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = 8:0.8:0.2:120, sodium polyaspartate is dissolved in 10 parts of water to form a sodium polyaspartate aqueous solution; then the nano titanium dioxide is ultrasonically dispersed in the remaining part of water at 40kHz to form a suspension, and then glutaraldehyde is added and dissolved evenly at 40kHz, and then the sodium polyaspartate aqueous solution is added, and mixed evenly at 40kHz, and centrifuged at 12000r / min for 25min, and the solid is taken, dried and dispersed to obtain the modified nano titanium dioxide.

[0058] The carboxylic acid monomer is acrylic acid (AA). The sulfonate monomer is sodium methyl allyl sulfonate (SMAS). The organic phosphorus compound is 2-phospho-1,2,4-tricarboxylic acid butane (PBTCA). The oxidative initiator is sodium persulfate. The reducing initiator is ascorbic acid. The azole derivative is benzotriazole (BTA). The regulator is ethylene glycol.

[0059] The preparation method of the composite multi-effect scale and corrosion inhibitor comprises the following steps:

[0060] S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A;

[0061] S2: Stir and mix the carboxylic acid monomer, reduced initiator and purified water according to their mass fractions, raise the temperature to 55°C, add the regulator and stir and mix evenly, continue to heat to 75°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to complete the dropping within 60 min, continue stirring and reacting for 3.5 h, cool to room temperature, add the azole derivative, stir and mix for 40 min, filter through a 150-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor.

[0062] Example 5

[0063] A composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 15 parts of carboxylic acid monomers, 15 parts of sulfonate monomers, 20 parts of organic phosphorus compounds, 1 part of modified chitosan, 6 parts of modified nano titanium dioxide, 1 part of oxidative initiator, 5 parts of reduced initiator, 1 part of azole derivatives, 10 parts of regulators and 10 parts of purified water.

[0064] The preparation method of modified chitosan comprises the following steps: using chitosan with a molecular weight range of 100,000 Da to 300,000 Da as a raw material; adding cerium chloride and glutaraldehyde into water to dissolve them uniformly according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = 12:0.5:0.4:100, then adding chitosan, mixing them uniformly by 40kHz ultrasonic dispersion, centrifuging at 10000 r / min for 15 minutes, taking the solid, drying and then breaking it up to obtain modified chitosan.

[0065] In the above technical scheme, the preparation method of the modified nano titanium dioxide is as follows: according to the mass ratio of nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = 8:0.3:0.2:100, sodium polyaspartate is dissolved in 10 parts of water to form a sodium polyaspartate aqueous solution; then the nano titanium dioxide is ultrasonically dispersed in the remaining part of water at 20kHz to form a suspension, and then glutaraldehyde is added and dissolved evenly at 20kHz ultrasound, and then the sodium polyaspartate aqueous solution is added, and mixed evenly at 20kHz ultrasound, and centrifuged at 12000r / min for 15min, and the solid is taken, dried and dispersed to obtain the modified nano titanium dioxide.

[0066] Among them, the carboxylic acid monomer is a mixture of acrylic acid (AA) and maleic acid (MA) in a mass ratio. The sulfonate monomer is a mixture of sodium allyl sulfonate (SAS) and sodium styrene sulfonate (SS) in a mass ratio. The organophosphorus compound is a mixture of aminotrimethylenephosphonic acid (ATMP) and 2-hydroxyphosphonoacetic acid (HPAA) in a mass ratio. The oxidative initiator is a mixture of sodium persulfate and ammonium persulfate in a mass ratio. The reduced initiator is a mixture of sodium bisulfite and ferrous sulfate in a mass ratio. The azole derivative is a mixture of methyl benzotriazole (TTA) and benzotriazole in a mass ratio. The regulator is a mixture of isopropanol and dodecyl mercaptan in a mass ratio.

[0067] The preparation method of the composite multi-effect scale and corrosion inhibitor comprises the following steps:

[0068] S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A;

[0069] S2: Stir and mix the carboxylic acid monomer, reduced initiator and purified water according to their mass fractions, heat to 55°C, add the regulator and stir and mix evenly, continue to heat to 70°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to complete the dropping within 60 min, continue stirring and reacting for 3 h, cool to room temperature, add the azole derivative, stir and mix for 40 min, filter through a 100-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor and corrosion inhibitor.

[0070] Example 6

[0071] A composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 12 parts of carboxylic acid monomers, 20 parts of sulfonate monomers, 11 parts of organic phosphorus compounds, 1.5 parts of modified chitosan, 3.5 parts of modified nano titanium dioxide, 4 parts of oxidative initiators, 4 parts of reduced initiators, 2 parts of azole derivatives, 6 parts of regulators and 0 parts of purified water.

[0072] The preparation method of modified chitosan comprises the following steps: using chitosan with a molecular weight range of 100,000 Da to 300,000 Da as a raw material; adding cerium chloride and glutaraldehyde into water to dissolve them uniformly according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = 10:1.2:0.3:100, then adding chitosan, mixing them uniformly by 30kHz ultrasonic dispersion, centrifuging at 6000r / min for 20min, taking the solid, drying and breaking it up to obtain modified chitosan.

[0073] In the above technical scheme, the preparation method of the modified nano titanium dioxide is as follows: according to the mass ratio, nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = 6:0.4:0.15:120), sodium polyaspartate is dissolved in 6 parts of water to form a sodium polyaspartate aqueous solution; then the nano titanium dioxide is ultrasonically dispersed in the remaining part of water at 30kHz to form a suspension, and then glutaraldehyde is added and ultrasonically dissolved at 30kHz to uniformly dissolve, and then the sodium polyaspartate aqueous solution is added, and ultrasonically mixed at 30kHz to uniformly mix, and centrifuged at 10000r / min for 20min, and the solid is taken, and it is dispersed after drying to obtain the modified nano titanium dioxide.

[0074] Among them, the carboxylic acid monomer is maleic acid (MA). The sulfonate monomer is a mixture of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and sodium methyl allyl sulfonate (SMAS) in equal mass ratios. The organophosphorus compound is a mixture of hydroxyethylidene diphosphonic acid (HEDP) and 2-phospho-1,2,4-tricarboxylic acid butane (PBTCA) in equal mass ratios. The oxidative initiator is hydrogen peroxide. The reducing initiator is a mixture of sodium hypophosphite and ascorbic acid in equal mass ratios. The azole derivative is a mixture of benzotriazole (BTA) and mercaptobenzothiazole (MBT) in equal mass ratios. The regulator is a mixture of dodecyl mercaptan, ethylene glycol and mercaptoethanol in equal mass ratios.

[0075] The preparation method of the composite multi-effect scale and corrosion inhibitor comprises the following steps:

[0076] S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A;

[0077] S2: Stir and mix the carboxylic acid monomer and the reduced initiator according to their mass fractions, heat to 50°C, add the regulator and stir and mix evenly, continue to heat to 70°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to complete the dropping within 60 min, continue stirring and reacting for 3.5 h, cool to room temperature, add the azole derivative, stir and mix for 20 min, filter through a 150-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor and corrosion inhibitor.

[0078] Example 7

[0079] A composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 13 parts of carboxylic acid monomers, 26 parts of sulfonate monomers, 14 parts of organic phosphorus compounds, 2.5 parts of modified chitosan, 5.5 parts of modified nano titanium dioxide, 4 parts of oxidative initiators, 3 parts of reduced initiators, 4 parts of azole derivatives, 7 parts of regulators and 12 parts of purified water.

[0080] The preparation method of modified chitosan comprises the following steps: using chitosan with a molecular weight range of 100,000 Da to 300,000 Da as a raw material; adding cerium chloride and glutaraldehyde into water to dissolve them uniformly according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = 9:1:0.3:120, then adding chitosan, mixing them uniformly with 40kHz ultrasonic dispersion, centrifuging at 10000r / min for 15 minutes, taking the solid, drying and breaking it up to obtain modified chitosan.

[0081] In the above technical scheme, the preparation method of the modified nano titanium dioxide is as follows: according to the mass ratio of nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = 7:0.7:0.1:110, sodium polyaspartate is dissolved in 9 parts of water to form a sodium polyaspartate aqueous solution; then the nano titanium dioxide is ultrasonically dispersed in the remaining part of water at 25kHz to form a suspension, and then glutaraldehyde is added and ultrasonically dissolved at 25kHz to form a suspension, and then the sodium polyaspartate aqueous solution is added and ultrasonically mixed at 25kHz to form a suspension, and then the sodium polyaspartate aqueous solution is added and ultrasonically mixed at 25kHz to form a suspension, and then the solid is centrifuged at 10000r / min for 25min, and the solid is taken, dried and then dispersed to obtain the modified nano titanium dioxide.

[0082] Among them, the carboxylic acid monomer is a mixture of acrylic acid (AA) and maleic acid (MA) in a mass ratio. The sulfonate monomer is a mixture of sodium allyl sulfonate (SAS), sodium styrene sulfonate (SS), 2-acrylamido-2-methylpropane sulfonic acid (AMPS) and sodium methyl allyl sulfonate (SMAS) in a mass ratio. The organophosphorus compound is a mixture of aminotrimethylenephosphonic acid (ATMP), 2-hydroxyphosphonoacetic acid (HPAA), hydroxyethylidene diphosphonic acid (HEDP) and 2-phospho-1,2,4-tricarboxylic acid butane (PBTCA) in a mass ratio. The oxidative initiator is a mixture of sodium persulfate, ammonium persulfate and hydrogen peroxide in a mass ratio. The reducing initiator is a mixture of sodium bisulfite, ferrous sulfate, sodium hypophosphite and ascorbic acid in a mass ratio. The azole derivative is a mixture of methyl benzotriazole (TTA), benzotriazole (BTA) and mercaptobenzothiazole (MBT) in a mass ratio. The regulator is a mixture of isopropanol, dodecyl mercaptan, ethylene glycol and mercaptoethanol in equal mass ratios.

[0083] The preparation method of the composite multi-effect scale and corrosion inhibitor comprises the following steps:

[0084] S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A;

[0085] S2: Stir and mix the carboxylic acid monomer, reduced initiator and purified water according to their mass fractions, heat to 55°C, add the regulator and stir and mix evenly, continue to heat to 70°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to complete the dropping within 60 min, continue stirring and reacting for 3.5 h, cool to room temperature, add the azole derivative, stir and mix for 20 min, filter through a 150-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor and corrosion inhibitor.

[0086] Comparative Example 1

[0087] No modified chitosan is added to the composite multi-effect scale and corrosion inhibitor; other parameters and methods are the same as in Example 1.

[0088] Comparative Example 2

[0089] In the composite multi-effect scale and corrosion inhibitor, the modified chitosan is replaced by chitosan; other parameters and methods are the same as in Example 1.

[0090] Comparative Example 3

[0091] No modified nano titanium dioxide is added to the composite multi-effect scale and corrosion inhibitor; other parameters and methods are the same as in Example 1.

[0092] Comparative Example 4

[0093] In the composite multi-effect scale and corrosion inhibitor, the modified nano titanium dioxide is replaced by nano titanium dioxide; other parameters and methods are the same as in Example 1.

[0094] Comparative Example 5

[0095] No modified chitosan or modified nano titanium dioxide is added to the composite multi-effect scale and corrosion inhibitor; other parameters and methods are the same as in Example 1.

[0096] Comparative Example 6

[0097] Modified chitosan and modified nano-titanium dioxide are not prepared. In the preparation method, after sieve filtration in S2, chitosan, cerium chloride, nano-titanium dioxide and sodium polyaspartate are directly added and mixed according to the mass fractions of Example 1 to obtain a composite multi-effect scale inhibitor and corrosion inhibitor; other parameters and methods are the same as Example 1.

[0098] Comparative Example 7

[0099] No azole derivatives are added to the composite multi-effect scale and corrosion inhibitor; other parameters and methods are the same as in Example 1.

[0100] The scale inhibition performance of the composite multi-effect scale and corrosion inhibitor of each of the above-mentioned embodiments and comparative examples was tested.

[0101] According to GB-T 16632 "Determination of scale inhibition performance of water treatment agents - Calcium carbonate deposition method", GB / T 22626 "Determination of scale inhibition performance of water treatment agents - Calcium phosphate deposition method" and GB / T 18175 "Determination of corrosion inhibition performance of water treatment agents - Rotating coupon method", calcium carbonate scale inhibition test, calcium phosphate scale inhibition experiment and rotating coupon corrosion test were carried out.

[0102] The water sample was taken from a petrochemical enterprise under high concentration multiples operating conditions, high pH, ​​high alkalinity, high temperature, and high hardness circulating cooling water system. The main water quality indicators during the test were chloride ion 1872 mg / L, total hardness 46.5 mmol / L (calculated as calcium carbonate), calcium hardness 1674 mg / L (calculated as calcium carbonate), pH=9.13, and alkalinity 396 mg / L (calculated as calcium carbonate).

[0103] The dosage of each composite multi-effect scale and corrosion inhibitor is 20ppm. The scale inhibition rate test results are shown in Table 1, and the corrosion rate results are shown in Table 2.

[0104] Table 1 Scale inhibition rate test results

[0105] Sample Calcium carbonate scale inhibition rate% Calcium phosphate scale inhibition rate% Example 1 97.82 98.47 Example 2 97.04 98.12 Example 3 97.23 98.36 Example 4 97.16 99.25 Example 5 98.18 98.83 Example 6 98.43 99.37 Example 7 98.72 99.41 Comparative Example 1 89.29 92.02 Comparative Example 2 93.14 94.62 Comparative Example 3 90.95 93.24 Comparative Example 4 94.07 95.63 Comparative Example 5 85.41 88.22 Comparative Example 6 91.96 93.78 Comparative Example 7 93.50 93.89

[0106] It can be seen from the above results that the composite multi-effect scale inhibitors and corrosion inhibitors of Examples 1 to 7 have more excellent scale inhibition capabilities, with a scale inhibition rate of more than 97% for calcium carbonate and more than 98% for calcium phosphate. It can be seen from the results of Comparative Examples 1 to 5 that modified chitosan has better scale inhibition capabilities than chitosan, and modified nano-titanium dioxide has better scale inhibition capabilities than nano-titanium dioxide. Without the addition of modified chitosan and modified nano-titanium dioxide, the scale inhibition capabilities are greatly reduced. It can be seen from the results of Comparative Example 6 that without modification, directly adding chitosan, cerium chloride, nano-titanium dioxide, and sodium polyaspartate for mixing will reduce the overall scale inhibition effect of the composite multi-effect scale inhibitor and corrosion inhibitor. It can be seen from the results of Comparative Example 7 that the scale inhibition capability of the composite multi-effect scale inhibitor and corrosion inhibitor is reduced without the addition of azole derivatives.

[0107] Table 2 Corrosion rate test results

[0108] Sample Carbon steel corrosion rate mm / a Brass corrosion rate mm / a Stainless steel corrosion rate mm / a Example 1 0.041 0.0031 0.0029 Example 2 0.044 0.0035 0.0033 Example 3 0.038 0.0033 0.0031 Example 4 0.042 0.0032 0.0032 Example 5 0.039 0.0029 0.0028 Example 6 0.043 0.0031 0.0032 Example 7 0.040 0.0029 0.0031 Comparative Example 1 0.043 0.0034 0.0032 Comparative Example 2 0.041 0.0032 0.0030 Comparative Example 3 0.044 0.0036 0.0034 Comparative Example 4 0.042 0.0032 0.0031 Comparative Example 5 0.047 0.0039 0.0036 Comparative Example 6 0.043 0.0034 0.0032 Comparative Example 7 0.052 0.0061 0.0041

[0109] It can be seen from the above results that the composite multi-effect scale inhibitors and corrosion inhibitors of Examples 1 to 7 have low corrosion rates for carbon steel sheets, brass sheets, and stainless steel sheets, and meet the standard requirements. It can be seen from the results of Comparative Examples 1 to 5 that modified chitosan and modified nano-titanium dioxide have a reducing effect on the corrosion rates of carbon steel sheets, brass sheets, and stainless steel sheets. It can be seen from the results of Comparative Example 6 that the effect of reducing the corrosion rate decreases when modified chitosan and modified nano-titanium dioxide are not prepared. It can be seen from the results of Comparative Example 7 that azole derivatives can reduce the corrosion rate.

Claims

1. A composite multi-effect scale and corrosion inhibitor, characterized in that: The composite multi-effect scale and corrosion inhibitor comprises the following raw materials in parts by weight: 5 to 15 parts of carboxylic acid monomers, 15 to 30 parts of sulfonate monomers, 10 to 20 parts of organic phosphorus compounds, 1 to 3 parts of modified chitosan, 2 to 6 parts of modified nano titanium dioxide, 1 to 5 parts of oxidative initiators, 1 to 5 parts of reduced initiators, 1 to 5 parts of azole derivatives, 5 to 10 parts of regulators and 0 to 30 parts of purified water; The preparation method of the modified chitosan comprises the following steps: according to the mass ratio of chitosan: cerium chloride: glutaraldehyde: water = (8-12): (0.5-2): (0.2-0.4): (100-120), cerium chloride and glutaraldehyde are added into water to be uniformly dissolved, then chitosan is added, ultrasonic dispersion is performed to mix uniformly, centrifugation is performed, solid is taken, and it is dried and then dispersed to obtain the modified chitosan; The carboxylic acid monomer is at least one of acrylic acid and maleic acid; the sulfonate monomer is at least one of sodium allyl sulfonate, sodium styrene sulfonate, 2-acrylamido-2-methylpropane sulfonic acid, and sodium methyl allyl sulfonate.

2. A composite multi-effect scale and corrosion inhibitor according to claim 1, characterized in that: The chitosan is high molecular weight chitosan with a molecular weight range of 100,000 Da to 300,000 Da; the frequency of the ultrasonic dispersion is 20 kHz to 40 kHz, the rotation speed of the centrifugal separation is 6000 r / min to 10000 r / min, and the time of the centrifugal separation is 15 min to 25 min.

3. A composite multi-effect scale and corrosion inhibitor according to claim 1, characterized in that: The preparation method of the modified nano titanium dioxide comprises the following steps: dissolving sodium polyaspartate in 5 to 10 parts of water according to the mass ratio of nano titanium dioxide: sodium polyaspartate: glutaraldehyde: water = (5 to 8): (0.3 to 0.8): (0.08 to 0.2): (100 to 120) to form a sodium polyaspartate aqueous solution; then ultrasonically dispersing the nano titanium dioxide in the remaining part of water to form a suspension, then adding glutaraldehyde to dissolve the suspension uniformly, then adding the sodium polyaspartate aqueous solution to mix the suspension uniformly by ultrasonic dispersion, centrifuging, taking the solid, drying and then breaking it up to obtain the modified nano titanium dioxide.

4. A composite multi-effect scale and corrosion inhibitor according to claim 3, characterized in that: The frequency of the ultrasonic dispersion is 20kHz to 40kHz, the rotation speed of the centrifugal separation is 10000r / min to 12000r / min, and the time of the centrifugal separation is 15min to 25min.

5. A composite multi-effect scale and corrosion inhibitor according to claim 1, characterized in that: The organic phosphorus compound is at least one of aminotrimethylenephosphonic acid, 2-hydroxyphosphonoacetic acid, hydroxyethylidene diphosphonic acid, and 2-phospho-1,2,4-tricarboxylic acid butane.

6. A composite multi-effect scale and corrosion inhibitor according to claim 1, characterized in that: The oxidative initiator is at least one of sodium persulfate, ammonium persulfate and hydrogen peroxide; the reducing initiator is at least one of sodium bisulfite, ferrous sulfate, sodium hypophosphite and ascorbic acid.

7. A composite multi-effect scale and corrosion inhibitor according to claim 1, characterized in that: The azole derivative is at least one of methyl benzotriazole, benzotriazole, and mercaptobenzothiazole; the regulator is at least one of isopropanol, dodecyl mercaptan, ethylene glycol, and mercaptoethanol.

8. A method for preparing a composite multi-effect scale inhibitor and corrosion inhibitor, used for preparing a composite multi-effect scale inhibitor and corrosion inhibitor as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1: Mixing the sulfonate monomer, the organophosphorus compound and the oxidative initiator according to their weight fractions to obtain a mixed solution A; S2: Stir and mix the carboxylic acid monomer, reduced initiator and purified water according to their mass fractions, raise the temperature to 50°C-55°C, add the regulator and stir and mix evenly, continue to heat to 70°C-75°C under nitrogen protection, add the mixed solution A dropwise, control the dropping speed to be within 50min-60min, continue to stir and react for 3h-3.5h, cool to room temperature, add the azole derivative, stir and mix for 20min-40min, filter through a 100-mesh-150-mesh sieve, take the filtrate, add modified chitosan and modified nano-titanium dioxide to the filtrate, mix, and obtain a composite multi-effect scale inhibitor.

Citation Information

Patent Citations

  • Corrosion and scale inhibitor as well as preparation method and using method thereof

    CN104193016A

  • Phosphorus-free scale and corrosion inhibitor and preparation method thereof

    CN110937698A

  • Composite phosphorus-free scale inhibitor and preparation method thereof

    CN116040820A

  • Preparation method of cerium modified chitosan phosphorus removal granular adsorbent

    CN109012610A

  • Cohering agent of chitosan copolymer

    KR1019900017635A

Cited By

  • Phosphorus-free scale and corrosion inhibitor and preparation method thereof

    CN120208440A

  • A phosphorus-free scale and corrosion inhibitor and its preparation method

    CN120208440B